Early 2nd trimester fetal demise in a monochorionic twin pregnancy: A cautionary tale. Issue 2 (May 2015) - Walsh, Colin A
Abstract: It is well established that the death of one fetus in a monochorionic twin pregnancy places the surviving twin at significant risk for neuro‐developmental delay or death. Although the early 1st trimester "vanishing twin" has not traditionally been considered a major risk, the precise gestational threshold beyond which a surviving twin is at risk remains uncertain. Most experts recommend serial ultrasounds and fetal MRI in the survivor, to look for evidence of ischaemic brain injury. We present a case of early monochorionic twin demise at 14–16 weeks, with evolving ventriculomegaly and ischaemic changes on fetal MRI in the co‐twin, leading to termination of pregnancy at 28 weeks.